Molecular variation of Trypanosoma brucei subspecies as revealed by AFLP fingerprinting - Agbo, E.E.C.; Majiwa, Phelix A.O.; Claassen, H.J.H.M.; Te Pas, M.F.W. (Cambridge University Press, 2002)
Genetic analysis of Trypanosoma spp. depends on the detection of variation between strains. We have used the amplified fragment length polymorphism (AFLP) technique to develop a convenient and reliable method for genetic characterization of Trypanosome (sub)species. AFLP accesses multiple independent sites within the genome and would allow a better definition of the relatedness of different Trypanosome (sub)species. Nine isolates (3 from each T. brucei subspecies) were tested with 40 AFLP primer combinations to identify the most appropriate pairs of restriction endonucleases and selective primers. Primers based on the recognition sequences of EcoRI and BglII were chosen and used to analyse 31 T. brucei isolates. Similarity levels calculated with the Pearson correlation coefficient ranged from 15 to 98%, and clusters were determined using the unweighted pair-group method using arithmetic averages (UPGMA). At the intraspecific level, AFLP fingerprints were grouped by numerical analysis in 2 main clusters, allowing a clear separation of T. b. gambiense (cluster I) from T. b. brucei and T. b. rhodesiense isolates (cluster II). Interspecies evaluation of this customized approach produced heterogeneous AFLP patterns, with unique genetic markers, except for T. evansi and T. equiperdum, which showed identical patterns and clustered together.